2005
DOI: 10.1111/j.0022-1112.2005.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal changes in the nekton of the Terminos Lagoon, Campeche, Mexico

Abstract: This study describes the current state of the nektonic communities in Terminos Lagoon in relation to the main environmental factors, and documents variations in number of fish species, dominance and abundance, compared to studies performed in 1980. Information on several environmental factors (temperature, salinity, oxygen, pH and transparency) in the Terminos Lagoon between October 1997 and March 1999 allowed the classification of the lagoon into five zones or subsystems. The hydrological characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
19

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 5 publications
2
24
0
19
Order By: Relevance
“…En primer lugar, se confirmó la agrupación de especies distinguida por el análisis de clúster y se destaca que S. testudineus, A. rhomboidalis, L. rhomboides y S. hispida se asociaron a las condiciones de día para las tres temporadas climáticas, mientras que el resto de las especies se asoció a las horas de noche. Ramos-Miranda et al, 2005). Sin embargo, para la costa norte de Campeche, la información es escasa y solo se ha reportado un comportamiento ambiental clasificado en dos épocas climáticas (Secas y Lluvias) (CONANP, 2006).…”
Section: (L Rhomboides)unclassified
“…En primer lugar, se confirmó la agrupación de especies distinguida por el análisis de clúster y se destaca que S. testudineus, A. rhomboidalis, L. rhomboides y S. hispida se asociaron a las condiciones de día para las tres temporadas climáticas, mientras que el resto de las especies se asoció a las horas de noche. Ramos-Miranda et al, 2005). Sin embargo, para la costa norte de Campeche, la información es escasa y solo se ha reportado un comportamiento ambiental clasificado en dos épocas climáticas (Secas y Lluvias) (CONANP, 2006).…”
Section: (L Rhomboides)unclassified
“…In such a critical ecosystem, recent concern has arisen that an increase in salinity related to climate change might be building up, detrimentally impacting juvenile developmental stages of exploited species (Ramos Miranda et al 2005a;2005b;Sosa Lopez et al 2005;Villéger et al 2010). Those authors observed a loss in functional diversity and a biotic homogenization in the fish community of Terminos Lagoon which they linked to a salinity increase between the years 1980-1981 and 1998-1999, and interpreted as a regular shift from hypohaline to euhaline/hyperhaline status due to climate change (Ramos Miranda et al 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Particularmente en la Laguna de Términos, en numerosos estudios se señala que la comunidad íctica está integrada por cerca de 100 especies, de las cuales 15 se consideran dominantes (Amezcua-Linares & Yáñez-Arancibia 1980, Yáñez-Arancibia & Day 1982, Ayala-Pérez et al 1993, Ramos-Miranda et al 2005. Dentro del sistema, las mojarras Diapterus rhombeus (Cuvier, 1829) y Eucinostomus gula (Quoy & Gaimard, 1824) han mostrado ser unas de las especies dominantes en número, peso y frecuencia de captura.…”
Section: Introductionunclassified